State Of The Immune System In Patients With Hospital Pneumonia In The Background Of Chronic Kidney Disease - Daminov Botir Turgunpulatovich, Daminova Lola Turgunpulatovna, Asadov Nodirjon Zakirovich, Muminov Davron Kadirovich (International Journal of Advanced Science and Technology, 2020)
Objective: to study some indicators of the immunohemogram in patients with community-acquired pneumonia on the background of CKD.